2019
DOI: 10.1177/1354816618823921
|View full text |Cite
|
Sign up to set email alerts
|

Structural model robustness checks in PLS-SEM

Abstract: Partial least squares structural equation modeling (PLS-SEM) has become a standard tool for analyzing complex inter-relationships between observed and latent variables in tourism and numerous other fields of scientific inquiry. Along with the recent surge in the method’s use, research has contributed several complementary methods for assessing the robustness of PLS-SEM results. Although these improvements are documented in extant literature, research on tourism has been slow to adopt the relevant complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
333
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 558 publications
(438 citation statements)
references
References 118 publications
6
333
0
3
Order By: Relevance
“…The analysis was carried out by employing variance-based SEM, using partial least squares [74,75] through the Smart-PLS 3.2.8 (Boenningstedt, Germany) software [76]. In recent years, partial least squares structural equation modeling (PLS-SEM) has shown its footprints over diversified disciplines including marketing, accounting, human resource management, and many others [77]. Rather than following the crowd, authors have preferred PSL-SEM for several reasons.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was carried out by employing variance-based SEM, using partial least squares [74,75] through the Smart-PLS 3.2.8 (Boenningstedt, Germany) software [76]. In recent years, partial least squares structural equation modeling (PLS-SEM) has shown its footprints over diversified disciplines including marketing, accounting, human resource management, and many others [77]. Rather than following the crowd, authors have preferred PSL-SEM for several reasons.…”
Section: Results and Analysismentioning
confidence: 99%
“…Relationships among the dependent and independent variables were assessed, while analyzing the structural model through the size and direction of path coefficients, values of the coefficient of determination, and t-values [77,86]. Following recent studies, we treated psychological empowerment and AME as higher order (single factor) constructs [12,63,66].…”
Section: Structural Model Evaluationmentioning
confidence: 99%
“…Moreover, the issue of endogeneity must be addressed by applying the right strategy and approach in testing the issue in organizational resilience studies, including the treatment of endogeneity through introducing the control variable of the ex-post assessment with an input variable [47]. Future studies can run complementary methods to establish whether or not the issue of endogeniety is critical for the study results [45].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, given the issue of endogeneity is critical in employing regression-based methods like PLS-SEM [45], the first test conducted in this study was for non-normality of the independent variables. The normality test revealed that the input variables were non-normal (see Section 3.4).…”
Section: Testing Endogenietymentioning
confidence: 99%
See 1 more Smart Citation